Uveitis: Classification, Etiologies and Clinical Signs - Aditya Shreekant Kelkar; Ekta Rakesh Arora; B. Sowkath; Jyotirmay Biswas (Delhi Journal of Ophthalmology)
Uveitis is one of the vision threatening eye diseases. There are several conditions that can mimic uveitis. An approach to uveitis should include uveitis oriented history, ophthalmic examination, systemic evaluation, ancillary tests and laboratory investigations. Various signs and symptoms can occur in different types of uveitis. There is a new grading system of anterior chamber inflammation and vitreous inflammation by SUN working group. There is also an anatomic and an etiological classification of uveitis. New classification systems have been proposed recently for intraocular tuberculosis, ocular sarcoidosis, Vogt-Koyanagi-Harada disease, Behcet's disease and acute retinal necrosis. This review article will update the clinical approach and various classification systems in uveitis.